Annual Review of Scalable Computing, Vol 4. - Yuen, C. K. (Series on scalable computing., 2002)
A collection of seven long articles, this book comprehensively discusses significant projects in scalable computing in various research organizations around the world. It represents the quantitative and qualitative growth of work in the area. Contents: Experiences with Shared Virtual Memory on System Area Network Clusters: System Simulation, Implementation, and Emulation; Average-Case Scalability Analysis of Parallel Computations; Parallel IO Prefetching and Caching; A C++/Tuple-Lock Implementation for Distributed Objects; Static Data Allocation and Load Balancing Techniques for Heterogeneous.